A quantum mechanical study of La-doped Pb(Zr,Ti)O-3 - Stashans, A. (2006)
Lanthanum-modified Pb(Zr,Ti)O3 (PZT) crystals have been investigated applying a quantum-mechanical approach based on the Hartree-Fock theory. A morphotropic phase boundary (MPB), PbZr0.53Ti0.47O3, of the crystal was considered throughout the study. The obtained results show the outward atomic displacements with respect to the La impurity within the defective region and also the increase of covalent nature in the chemical bonding of the material. These outcomes are discussed and analyzed in light of the available experimental data. The occurrence of Jahn-Teller self-trapped electron polarons is predicted in the present report. © 2006 Elsevier B.V. All rights reserved.